Chemical composition, anticancer and antibacterial activity of Nepeta mahanensis essential oil - Mahla Amirzadeh; Sara Soltanian; Neda Mohamadi (BMC, 2022)
Abstract Background Conventional cancer treatments, such as chemotherapy, radiation therapy, and surgery, often affect the patients' quality of life due to their serious side effects, indicating the urgent need to develop less toxic and more effective alternative treatments. Medicinal plants and their derivatives are invaluable sources for such remedies. The present study aimed to determine the chemical composition, anticancer and antibacterial activities of Nepeta mahanesis essential oil (EO). Methods The chemical composition of EO was analyzed by gas chromatography-mass spectrometry (GC-MS). Cytotoxicity and apoptosis/necrosis induction of EO was analyzed by MTT assay and Flow cytometry. Real-time PCR was performed to evaluate the Bax/Bcl2 gene expression. Also, the effect of the EO on the cells' mitochondrial membrane potential (MMP) and ROS level was assessed. DPPH assay was done to assess the free radical scavenging activity of the EO. The Antimicrobial activity, MIC, and MBC of the oil were determined via well-diffusion and broth microdilution methods. Results Based on the GC-MS analysis, 24 compounds were identified in the EO, of which 1,8-cineole (28.5%), Nepetalactone (18.8%), germacrene D (8.1%), and β-pinene (7.2%), were the major compounds. Also, the EO showed considerable cytotoxicity against MCF-7, Caco-2, SH-SY5Y, and HepG2 after 24 and 48 h treatment with IC50 values between 0.0.47 to 0.81 mg/mL. It was revealed that this compound increased the Bax/Bcl2 ratio in the MCF-7 cells and induced apoptosis (27%) and necrosis (18%) in the cells. Moreover, the EO treatment led to a substantial decrease in MMP, which is indicative of apoptosis induction. A significant increase in ROS level was also detected in the cells following exposure to the EO. This compound showed strong DPPH radical scavenging activity (IC50: 30). It was also effective against Gram-positive E. faecalis (ATCC 29,212) and Gram-negative E. coli (ATCC 11,333) bacteria. Conclusions The results of this study demonstrated that the EO of N. mahanesis could be considered a bioactive product with biomedical applications that can be used as an alternative cancer treatment and applied in the biomedical industries.